Arbuscular Mycorrhizal Community in Roots and Nitrogen Uptake Patterns of Understory Trees Beneath Ectomycorrhizal and Non-ectomycorrhizal Overstory Trees - Tatsumi, Chikae; Hyodo, Fujio; Taniguchi, Takeshi; Shi, Weiyu; Koba, Keisuke; Fukushima, Keitaro; Du, Sheng; Yamanaka, Norikazu; Templer, Pamela; Tateno, Ryunosuke (Frontiers in Plant Science, 2021)
Nitrogen (N) is an essential plant nutrient and plants can take up N from several sources, including via mycorrhizal fungal associations. The N uptake patterns of understory plants may vary beneath different types of overstory trees, especially through the difference in their type of mycorrhizal association (arbuscular mycorrhizal; AM or ectomycorrhizal; ECM), because soil mycorrhizal community and N availability differ beneath AM (non-ECM) and ECM overstory trees (e.g. relatively low nitrate content beneath ECM overstory trees). To test this hypothesis, we examined six co-existing AM-symbiotic understory tree species common beneath both AM-symbiotic black locust (non-ECM) and ECM-symbiotic oak trees of dryland forests in China. We measured AM fungal community composition of roots and natural abundance stable isotopic composition of N (δ15N) in plant leaves, roots, and soils. The root mycorrhizal community of understory trees differed between non-ECM and ECM overstory trees in response to soil N availability and root mycorrhizal community of overstory trees, although the extent depended on the understory tree species. Understory trees beneath non-ECM overstory trees had similar δ15N values in leaves and soil nitrate, suggesting that they took up most of their nitrogen as nitrate. Beneath ECM overstory trees , understory trees had consistently lower leaf than root δ15N, suggesting they depended on mycorrhizal fungi for N acquisition since mycorrhizal fungi transfer isotopically light N to host plants. Additionally, leaf N concentrations in the understory trees were lower beneath ECM than the non-ECM overstory trees. Our results show that the root mycorrhizal community and the N uptake patterns of understory trees vary beneath different overstory trees, due to differences in their type of mycorrhizal association.